ETXANlZ, Nemesio. Lan Hautatuak: Hiria argit., 2002 urtea, 268 or. (M, Atxaga, G. Etxeberria eta P. Suduperen ardurapean). - Mujika, Luis Maria (EGAN, 2021)
LUIS MARIA MUJIKA: ETXANlZ, Nemesio. Lan Hautatuak Hiria argit., 2002 urtea, 268 or. (M, Atxaga, G. Etxeberria eta P. Suduperen ardurapean).